2014 IEEE World Forum on Internet of Things (WF-IoT) 2014
DOI: 10.1109/wf-iot.2014.6803139
|View full text |Cite
|
Sign up to set email alerts
|

Human Data Interaction in IoT: The ownership aspect

Abstract: Abstract-As Internet of Things (IoT) becomes a growing reality, more ubiquitous devices are embedded in our daily lives, serving us in a broad range of purposes in everyday life from: personal healthcare to home automation to tailored smart city services. These devices primarily collect data that is about or produced by people, be it street noise level of a neighbourhood, or the energy footprint of an individual's home or her location and other situational context. As this unprecedented amount of data is colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Spiekermann and Novotny [31] have shown that in the absence of these explicit permissions an opaque shadow market in personal information has emerged. A transparent regulation framework also encourages individuals to share their information, adding to thickness in the market [19].…”
Section: Design Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Spiekermann and Novotny [31] have shown that in the absence of these explicit permissions an opaque shadow market in personal information has emerged. A transparent regulation framework also encourages individuals to share their information, adding to thickness in the market [19].…”
Section: Design Parametersmentioning
confidence: 99%
“…There is an extensive body of research into areas which are relevant to the design of a workable PPIM such as: data ownership [19,20] and privacy [21,22], personal informatics [23,24], the collection and modelling of personal information [25,26] and data security [27,28]. However "there is a substantial lack of empirical research on … markets for online personal data" [29] and most market design research is qualitative [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into markets in personal information is multi-dimensional and cross-disciplinary and touches on numerous areas of related research such as: data ownership [24,25], privacy [26,27], personal informatics [28,29], the collection and modelling of personal information [30,31] and data security [32,33]. However, as noted by e-market scholars, "there is a substantial lack of empirical research on … markets for online personal data" [34] and most market design research is qualitative [35].…”
Section: Introductionmentioning
confidence: 99%
“…By focusing on the type of relationship which exists between the individual and the company, they developed a four-space model of personal information management. It has also been proposed that individuals receive compensation for allowing their data to be included in a sample from which the buyer sought to infer a statistic of interest about a population [37] and for the allowing access to sensor data generated by the Internet of Things [24].…”
Section: Introductionmentioning
confidence: 99%